A critical review of the current knowledge regarding the biological impact of nanocellulose. Issue 1 (December 2016) - Endes, C.; Camarero-Espinosa, S.; Mueller, S.; Foster, E.; Petri-Fink, A.; Rothen-Rutishauser, B.; Weder, C.; Clift, M.
Abstract Several forms of nanocellulose, notably cellulose nanocrystals and nanofibrillated cellulose, exhibit attractive property matrices and are potentially useful for a large number of industrial applications. These include the paper and cardboard industry, use as reinforcing filler in polymer composites, basis for low-density foams, additive in adhesives and paints, as well as a wide variety of food, hygiene, cosmetic, and medical products. Although the commercial exploitation of nanocellulose has already commenced, little is known as to the potential biological impact of nanocellulose, particularly in its raw form. This review provides a comprehensive and critical review of the current state of knowledge of nanocellulose in this format. Overall, the data seems to suggest that when investigated under realistic doses and exposure scenarios, nanocellulose has a limited associated toxic potential, albeit certain forms of nanocellulose can be associated with more hazardous biological behavior due to their specific physical characteristics.